Principles of existential experience group - Kočiūnas, R. (Psichologija, 1991)
Our preparatory programme for counsellors includes group training with special stress on the problems of personal authenticity, freedom, responsibility, choice-making, guilt, love, suffering, intimacy, and inner silence. The aim here shall be more experiential than discussion-based group life that reveals itself through the moments and the existential problems arising „here and now" as well as their manifestation in everyday life. Participants are oriented toward the very proceeding of the group process. Simultaneously a constant feedback of the process by means of sharing feelings, with attention at every moments on “What am I feeling now?”, coupled with the analysis of the dynamics taking place shall be provided. The main principle of the group experience is such: priority is given not to interpersonal, but to intrapersonal dynamics, i.e. to explore oneself. During the course of the group an attempt shall be made at “meeting with oneself” at multifarious “here and now” moments.